Modeling DNA Double-Strand Break Repair Kinetics as an Epiregulated Cell-Community-Wide (Epicellcom) Response to Radiation Stress - Bobby R. Scott (SAGE Publishing, 2011)
The multicellular signaling model (MULTISIG1) was recently introduced to simulate the kinetics of repair of DNA double-strand breaks (DSBs) that were induced in confluent (non-dividing) cultured cells by a very low radiation dose where at most a single induced DSB would be expected in a given cell nucleus. The repair kinetics was modeled as representing what is now called an epi genetically-regulated (epiregulated) cell - com munity-wide ( epicellcom ) response to radiation stress. DSB repair initiation is assumed to require a threshold number of cells with DSBs participating in intercellular stress-response signaling. The MULTISIG1 model is extended in this study to apply to moderate doses where several DSBs can occur on the same DNA molecule. The repair of multiple breaks on the same molecule is treated as sequential stochastic events. For cells of differing genetic characteristics and epigenetic statuses, relationships are provided for evaluating the relative susceptibility ( RS ) for DSB induction, relative repair capacity ( RRC ) for DSB repair, and relative epiapoptosis capacity ( REC ), for epigenetically regulated apoptosis. The modified MULTISIG1 model is used to characterize the expected repair kinetics for confluent, human lung fibroblasts (MRC-5 line) briefly exposed in vitro to 90-kV x-rays. Possible application of the model to biological dosimetry is also discussed.